Assessment of oil-interceptor performance for solid removal in highway runoff. Issue 2 (15th January 2023) - Zakharova, Julia; Pouran, Hamid; Wheatley, Andrew; Arif, Mohammed
ABSTRACT: Oil interceptors are traditional SuDS devices used in highway runoff treatment to remove both floatable impurities (leaves, oil) and total suspended solids (TSS). This paper presents the results of an examination of the performance of an oil interceptor based on particle size distribution (PSD) and TSS during three rainfall events. The interceptor is situated on one of the busiest motorways in the UK (where peak traffic flow is 30, 000 vehicles per hour). Although the overall data collected for this study provided evidence that the interceptor removed, in most cases, 70% of TSS, the data for particle size distribution (PSD) showed that the interceptor did not always cope with particle separation for particles of less than 25 μm diameter. GRAPHICAL ABSTRACT: UF0001